Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV METEOR during cruise M78/3B - Gerold Wefer; Federico Damián Esteban; Benedikt Preu (PANGAEA, 2022)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg (Simrad) EM 120 multibeam echosounder was almost continuously recorded during RV METEOR cruise M78/3B. Data was recorded on 16 days between 2009-06-20 and 2009-07-05. This dataset contains a survey about 250km east of the Río de la Plata. The approximate average depth of the entire dataset is around 2200m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. However, also data analysis of the multibeam raw data revealed that SVP has not been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).